Development of augmented reality-based physics learning media on magnetic field - Muhammad Sholeh; Zeni Haryanto; Zulkarnaen Zulkarnaen (Universitas PGRI Kanjuruhan Malang, 2024)
Physics is a science that is the basis for technological developments. Physics consists of many abstract concepts that make it difficult for students to understand—for example, magnetic field matter. Therefore, learning media could deliver information to students are needed. It allows teachers to design various learning media through dynamic representations such as Augmented Reality or AR. This study aims to determine the feasibility and response of students to AR-based learning media on the topic of magnetic field development. This research is R&D type with an ADDIE model. The validators are media experts, two material experts, and an educator validating upon feasibility test. Then, 96 12th-grade students as research subjects in the product trial stage to obtain student responses. The feasibility test results from the media aspect are 91%, and the material aspect is 89%, which overall is 90% in the very feasible category. The product trial results found that student response was 85% in the very good category. Based on the study's results, AR-based learning media on magnetic fields is feasible to support physics learning.